FIRST-LINE PHARMACOTHERAPY OF CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY - Krtinic, Dane A; Lučić Prokin, Aleksandra; Conić, Irena; Todorović Mitić, Mirjana; Radić, Milica; Binić, Iva; Cekić, Miodrag; Jovanović, Hristina; Trajković, Hristina; Čevrljaković, Milan (Acta medicae Medianae, 2026)
Chemotherapy-induced peripheral neuropathy (CIPN) is a very common adverse event iatrogenically caused by the administration of neurotoxic chemotherapy protocols in oncology patients. Of the chemotherapeutics—oxaliplatin, cisplatin, carboplatin, docetaxel, paclitaxel, vinblastine and vincristine—bortezomib shows the greatest neurotoxicity. Recommendations for the first line of pharmacotherapy of this side effect of chemotherapy are gabapentinoids (pregabalin and gabapentin), antidepressants (amitriptyline, duloxetine, venlafaxine, desvenlafaxine), as well as topical application of lidocaine. Adequate pharmacotherapy of CIPN implies an individualized approach for each patient and compliance with guidelines for recommended first-line pharmacotherapy, first, in the form of monotherapy and later, depending on tolerability and achieved analgesic response, in the form of polytherapy with first-line drugs. If there is no adequate analgesic response to polytherapy with first-line drugs, only then is it necessary to switch to the second line of therapy. Treatment of CIPN leads to an adequate quality of life due to the reduction of the neuropathic component of pain, a reduction in depression and anxiety and the expected completion of the planned chemotherapy cycles, and consequently, a better prognosis of the underlying oncological disease of these patients.
Keywords: chemotherapy, peripheral neuropathy, pharmacotherapy